2021
DOI: 10.1002/joc.7142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiple reanalyses in reproducing the spatio‐temporal variability of temperature and precipitation indices over southern South America

Abstract: Several temperature and precipitation indices, with special focus on extremes, were analysed in different sub‐regions of southern South America during 1979–2017 using multiple reanalyses, the CPC gridded data set and the most extended network of meteorological stations employed in regional climate studies up to date. Reanalyses generally well represented the spatial patterns of the indices, although they showed some differences in extreme indices over large portions of southern South America and tended to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…Therefore, we conclude that precipitation estimates from ERA5 may be better suited for remote sites that do not have nearby gauge data. A recent study evaluating multiple reanalyzes (ERA5, ERAI, JRA55, and NCEP Reanalysis versions 1 and 2) over southern South America also finds ERA5 wet biases in some areas, while noting overall improvements over ERAI (Balmaceda‐Huarte et al., 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we conclude that precipitation estimates from ERA5 may be better suited for remote sites that do not have nearby gauge data. A recent study evaluating multiple reanalyzes (ERA5, ERAI, JRA55, and NCEP Reanalysis versions 1 and 2) over southern South America also finds ERA5 wet biases in some areas, while noting overall improvements over ERAI (Balmaceda‐Huarte et al., 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Of the 37 provided vertical pressure levels, 24 were considered for running the simulations (from 10 to 1000 hPa). ERA5 is suitable to pro-vide initial and boundary conditions as recent studies showed realistic spatial patterns of the temperature and precipitation over South America improving the precursor product ERA-Interim (Balmaceda-Huarte et al, 2021) and reduced biases compared to other reanalyses (Hassler and Lauer, 2021). No nudging was applied to the input data.…”
Section: Wrf Modelmentioning
confidence: 99%
“…The changes in frequency and intensity are not uniform in space and vary by region due to the different interacting drivers in extreme precipitation changes [8][9][10][11]. Tabari et al [8] showed that the changes in floods and extreme precipitation worldwide have intensified in response to global warming.…”
Section: Introductionmentioning
confidence: 99%